A wireless navigation and healthcare system for group recreational cycling. (20th August 2014) - Yu, Kun–Ming; Lee, Chi–Chung; Hsieh, Hung–Nien; Chang, Hsin–Wen; Zhou, Jiayi; Yu, Cheng–Yan; Liu, Jian–Yuan; Lee, Ming–Gong
Group recreational cycling (GRC) is a new kind of tourism activity involving a courier and a number of tourists. In addition to cyclists' safety and comfort, tracking their position, monitoring their health condition in terms of heart rate, guiding and warning along the way if necessary, are important in GRC. Information exchange among cyclists is essential to achieve above goals. In this paper, an event–based wireless navigation and healthcare system (EWS) for GRC using an Ad Hoc network with multi–hop protocol to transmit data among devices is proposed. EWS can be implemented to design suitable routes, to warn about bad road conditions, to play multimedia attractions for guiding, track cyclists' position and to monitor members' heart rate. System structure and design for EWS are given. Two scenarios are shown to demonstrate and to show the feasibility of EWS.